Sacituzumab Govitecan in Hormone Receptor-Positive/Human Epidermal Growth Factor Receptor 2-Negative Metastatic Breast Cancer - Rugo, Hope S.; Bardia, Aditya; Marmé, Frederik; Cortes, Javier; Schmid, Peter; Loirat, Delphine; Trédan, Olivier; Ciruelos, Eva; Dalenc, Florence; Pardo, Patricia Gómez; Jhaveri, Komal L.; Delaney, Rosemary; et al. (Journal of clinical oncology, 2022)
PURPOSE - - Hormone receptor-positive (HR+) human epidermal growth factor receptor 2-negative (HER2-) endocrine-resistant metastatic breast cancer is treated with sequential single-agent chemotherapy with poor outcomes. Sacituzumab govitecan (SG) is a first-in-class antibody-drug conjugate with an SN-38 payload targeting trophoblast cell-surface antigen 2, an epithelial antigen expressed in breast cancer. - - METHODS - - In this global, randomized, phase III study, SG was compared with physician's choice chemotherapy (eribulin, vinorelbine, capecitabine, or gemcitabine) in endocrine-resistant, chemotherapy-treated HR+/HER2- locally recurrent inoperable or metastatic breast cancer. The primary end point was progression-free survival (PFS) by blinded independent central review. - - RESULTS - - Patients were randomly assigned to receive SG (n = 272) or chemotherapy (n = 271). The median age was 56 years, 95% had visceral metastases, and 99% had a prior cyclin-dependent kinase 4/6 inhibitor, with three median lines of chemotherapy for advanced disease. Primary end point was met with a 34% reduction in risk of progression or death (hazard ratio, 0.66 [95% CI, 0.53 to 0.83; P = .0003]). The median PFS was 5.5 months (95% CI, 4.2 to 7.0) with SG and 4.0 months (95% CI, 3.1 to 4.4) with chemotherapy; the PFS at 6 and 12 months was 46% (95% CI, 39 to 53) v 30% (95% CI, 24 to 37) and 21% (95% CI, 15 to 28) v 7% (95% CI, 3 to 14), respectively. Median overall survival (first planned interim analysis) was not yet mature (hazard ratio, 0.84; P = .14). Key grade ≥ 3 treatment-related adverse events (SG v chemotherapy) were neutropenia (51% v 38%) and diarrhea (9% v 1%). - - CONCLUSION - - SG demonstrated statistically significant PFS benefit over chemotherapy, with a manageable safety profile in patients with heavily pretreated, endocrine-resistant HR+/HER2- advanced breast cancer and limited treatment options.
Gesehen am 01.02.2023